2022
DOI: 10.1002/art.42009
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Gut Microbiota and Elevated Serum Urate in Two Independent Cohorts

Abstract: Objective Hyperuricemia is a precursor to gout and is often present in other metabolic diseases that are promoted by microbiome dysbiosis. We undertook this study to examine the association of gut microbiota with hyperuricemia and serum urate levels in humans. Methods Study participants were derived from a community‐based observational study, the Xiangya Osteoarthritis Study (discovery cohort). Hyperuricemia was defined as the presence of a serum urate level >357 μmoles/liter in women and >416 μmoles/liter in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
47
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 60 publications
(56 citation statements)
references
References 49 publications
7
47
2
Order By: Relevance
“…This study shows, for the first time, that CEs significantly increase the UA content in urine, possibly as a result of abnormal metabolism. Studies have shown that UA is a biomarker of the oxidative stress state of the intestinal environment (Wang et al, 2022). Our results indicate that the intestine might be under oxidative stress in people in CEs.…”
Section: Discussionsupporting
confidence: 49%
See 1 more Smart Citation
“…This study shows, for the first time, that CEs significantly increase the UA content in urine, possibly as a result of abnormal metabolism. Studies have shown that UA is a biomarker of the oxidative stress state of the intestinal environment (Wang et al, 2022). Our results indicate that the intestine might be under oxidative stress in people in CEs.…”
Section: Discussionsupporting
confidence: 49%
“…The generation of intestinal ROS is related to physiological activities such as mood changes and insomnia (Brainard et al, 2016;Palinkas and Suedfeld, 2021). Studies have shown that intestinal cells secrete uric acid (UA) upon hydrogen peroxide stimulation to resist oxidative stress and that the increase in UA is related to imbalances in the gut microbiota (Wang et al, 2022). Some CE-simulation experiments show that light, gas, and work rhythms significantly affect the psychological states of the subjects, in turn affecting their cognitive abilities, teamwork, and other aspects of work efficiency (Berg et al, 2005;Kimhi, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Patients with HUA had reduced microbiota richness and diversity, an altered composition, and a lower relative abundance of Coprococcus than the normal controls ( Wei and Zhang, 2022 ). The probiotics Faecalibacterium , Gemmiger , Bacteroides , Roseburia , Bifidobacterium , and Akkermansia were significantly increased in asymptomatic HUA patients compared to the controls ( Yang et al., 2021 ).…”
Section: Characteristics Of the Gut Microbiota In Patients With Hua A...mentioning
confidence: 99%
“…Gout has higher relative abundances of Prevotella and Bacteroides while lower relative abundances of Enterobacteriaceae , which might cause uric acid degradation dysfunction and the buildup of uric acid in gout ( Chu et al., 2021 ). Additionally, the greater serum urate (SU) level was closely connected to the lower relative abundance of Faecalibacterium in hyperuricemia ( Wei et al., 2021 ).…”
Section: Dysbiosis and Goutmentioning
confidence: 99%
“…A study through the Kyoto Encyclopedia of Genes and Genomes (KEGG) metabolic pathway analysis revealed significant differences in amino acid metabolism (phenylalanine, tyrosine and tryptophan biosynthesis, D-glutamine and D-glutamate metabolism, and phosphate and phosphonate metabolism) and nucleotide metabolism (purine metabolism) between hyperuricemia and healthy controls. The gut microbiota’s metabolic dysfunction may influence serum uric acid levels through its impact on host metabolites ( Wei et al., 2021 ). The production of SCFAs (concentrations of acetate, propionate, and butyrate) derived from the gut microbiota in mice positively correlates with the effectiveness of treating hyperuricemia.…”
Section: Dysbiosis and Goutmentioning
confidence: 99%